Educational Supervision as a Strategic Mechanism for Improving Instructional Quality - Intan Nurhasanah; Eva Dianawati Wasliman (Al-Qalam Institue, 2026)
This study aims to examine the implementation of educational supervision based on Edward Deming’s Total Quality Management (TQM) principles in improving learning quality. A qualitative research design was employed, utilizing interviews, observations, and document analysis to capture supervisory practices. Data were analyzed using the Plan–Do–Check–Act (PDCA) cycle as a framework for supervision quality management. The findings reveal that educational supervision is implemented systematically through structured planning, professional execution, evidence-based evaluation, and continuous follow-up. The Check and Act stages play a critical role in strengthening teacher professionalism, fostering reflective practices, and sustaining a culture of quality improvement. These stages enable supervisors to use evaluative data as a basis for corrective actions and continuous development. The study implies that integrating TQM principles into educational supervision can transform supervision from a predominantly administrative function into a strategic mechanism for enhancing instructional quality. This research contributes both conceptually and practically to the development of supervision quality management in secondary education.